FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yunia Putri Lukitasari; Andi kartika (Dinamika Akuntansi Keuangan dan Perbankan, 2014)
The purpose of this reseach is to examine influence of Third Party Funds, Operating Expanse to Operating Income, CapitalAdequacy Ratio, Loan to Deposit Ratio, Non Performing Loan throught financial performance of public banking listed atIndonesian Stock Exchange during 2010-2012. Population of this research are Commercial Bank that resgistered inIndonesian Stock Exchange from 2010 till 2012. Data on this research are coming from Indonesian Stock Exchange (ISX).Sample are choosen by purposive sampling method at least 27 company. Data’s test technique by using multiple linearregression analyze. The result showed that the Thirt Party Funds, Capital Adequacy Ratio and Non Performing Loan hasno effect on Return On Asset,Operating Expenses to Operating Income negatively effect the Return On Asset and Loan toDeppoosit Ratio has a positive effect on Return On Asset.Keyword: thirt party funds, operating expense to operating income, capital adequacy ratio, loan to deposit ratio, nonperforming loan and return on asset.